Indigencia y productividad en el campo mexicano. Reseña de tres obras. Gustavo Esteva: The Struggle for Rural Mexico. ; Steven E. Sanderson: The Transformation of Mexican Agriculture: International Structure and the Politics of Rural Change. ; Merilee S. Grindle: State and Countryside: Development Policy and Agrarian Politics in Latin America. - Freebairn, D. K. (Revista Mexicana de Sociología, 2024)
-